2017
DOI: 10.22608/apo.2015166
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Glaucoma in Central India: A Hospital-Based Study

Abstract: Awareness of glaucoma in India is low. Lack of education and lower socioeconomic status are the major risk factors for late preentation of glaucoma. Continuous presence of a low level of awareness and the same factors accounting for it warrants the need for an aggressive and refined approach to increase awareness of glaucoma to prevent glaucoma-related blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Shrestha et al 49 found that family, relatives, and friends suffering from the condition and not suffering from the condition were the second and third most common sources of information. Maharana et al 50 reported that close acquaintance was the most common source of information.…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al 49 found that family, relatives, and friends suffering from the condition and not suffering from the condition were the second and third most common sources of information. Maharana et al 50 reported that close acquaintance was the most common source of information.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 86.9% of them had seen an ophthalmologist less than 10 times in their lives. Respondents' largest source of information was found to be "word of mouth" from family and friends which was the same case for many other studies [7][8][9][10]. This information points out to two facts, first the potential benefit that could be accrued from using glaucoma patients as a source of awareness to society and second the need for health care workers, healthrelated agencies and media to be more involved with the burning issue.…”
Section: Discussionmentioning
confidence: 54%
“…There have been very few studies showing the association of late presenting glaucoma with social variables and poor awareness [5,6]. Currently there is no feasible screening test and the only way to detect glaucoma early is to increase awareness among the population [7,8]. Studies conducted in developing countries have highlighted the lack of this quality in public [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…An Iranian population-based survey demonstrated that only 46.6% demonstrated glaucoma awareness while only 19.2% were able to correctly define the disease [ 29 ]. Asian countries, the likes of Nepal and India, demonstrated low rates of glaucoma knowledge among hospital presenting patients ranging from 1.9% to 27% [ 30 32 ]. China, on the other hand, demonstrated that 51.6% of glaucoma patients visiting a tertiary university hospital were aware of their disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%